Catholic theological ethics in the world church the plenary papers from the first cross-cultural conference on Catholic theological ethics - Keenan, James F. (Quezon City Ateneo de Manila University Press, 2008)
"A compilation of the plenary papers at the First Cross-cultural Conference on Catholic Theological Ethics in Padua, Italy. The panelists from five continents sought to answer the following questions: What are our moral challenges; how are we responding; and what hope do we have for the future?"--Publisher's description.
Introduction : the Conference at Padova / James F. Keenan -- Part I. How can theological ethicists respond to the world's needs? -- The needs of the world and the signs of the times : the challenge of human rights / Antonio Papisca -- Challenges of economic activity in a global world / Adela Cortina -- Universal declaration on bioethics and human rights / Henk ten Have -- Part II. Moral theology on the five continents -- The main "building sites" of ethics in West Africa / Mawuto R. Afan -- Locating the church among the wretched of the earth / Laurenti Magesa -- Authenticity and credibility : moral challenges after the African synod / Sebastien Muyengo Mulombe -- Moral challenges and the church in Asia today, with a specific consideration of Korea / Thomas Hong-Soon Han -- Globalization and Catholic theological ethics : a Southeast Asian perspective / Agnes M. Brazal -- Doing Christian ethics in India's world of cultural complexity and social inequality / Clement Campos -- Theological ethics in Europe (especially Southern Europe) : past, present and future / Marciano Vidal -- Political-ethical challenges in Europe : A Christian socio-ethical perspective / Marianne Heimbach-Steins -- On stem cells and homophobia / Piotr Mazurkiewicz -- Dreaming to a new moral theology for Brazil / Ronaldo Zacharias -- Hope in the midst of enormous challenges in Mexico / Sebastian Mier -- Moral reflection in Latin America : challenges and proposals within the Chilean reality / Tony Mifsud -- Catholic ethics in a world church : a U.S. view / David Hollenbach -- Due process and the rule of law : a moral/theological challenge / Jean Porter -- The challenge of world poverty : continuity and change in theological ethics from a Canadian perspective / Kenneth R. Melchin -- Part III. The central themes -- I. Hermeneutics and the sources of theological ethics -- Suffering and theological ethics : intimidation and hope / Robert Gascoigne -- Hermeneutics and the Sources of Theological Ethics / Maureen Junker-Kenny -- What will you have me do for you? (the theological ethics agenda from an Asian perspective) / Dionisio M. Miranda -- II. Sensus fidelium and moral discernment -- Has the concept of sensus fidelium fallen into desuetude? / Paul Valadier -- Sensus fidelium and moral discernment : the principle of inculturation and of love / Nathanael Yaovi Soede -- The sensus fidelium and moral discernment / Giuseppe Angelini -- III. The challenge of pluralism and the future of moral theology -- The challenge of pluralism / Eberhard Schockenhoff -- Moral theology : from evolutionary to revolutionary change / Lisa Sowle Cahill -- Community and pluralism : challenges to moral theology / Marcio Fabri dos Anjos -- Part IV. Globalization and justice -- Globalization and justice : new horizons for moral theology / Enrico Chiavacci -- Globalization needs to count human persons / Vimal Tirimanna -- A call for prophetic action / John Mary Waliggo.
Published by arrangement with The Continuum International Publishing Group.
Keywords: Christian ethics -- Catholic authors -- Congresses